KONTROL FASIES DAN STRUKTUR DALAM PEMBENTUKAN REKAHAN ALAMI PADA BATUGAMPING, RAJAMANDALA, DAERAH GUNUNG BENDE, PADALARANG, JAWA BARAT - Jannata Saputra, Isto
Naturally fracture reservoir in carbonated rocks has been proven as major agent in many hydrocarbon fields in Indonesia. Mainly, natural fractures act as key control in reservoir quality. In natural fractures reservoir, heterogeneity became a main problem, therefore, study about fractures type, density, fracture distribution and connectivity are important to understand these heterogeneity. Gunung Bende mining area in Padalarang District, West Java, have well pe\reserve carbonate rocks. This Rajamandala Formation have Oligo-Miocene in ages and lithologhical character are Framstone-Bindstone Facies Association. In structural term, this area located at southern limb of Rajamandala Thrust Fault anticline. Scanline method are use to obtained fracture data in the outcrop area. Scanline located at three different areas with five-measurement line. Headcoral-platycoral framestone and platicoral bindstone are two main facies that compose lithological character of Bende Mining Area. Some minor strike slip fault are recognized and act as structural manifestation of left lateral fault in the east of Gunung Bende Mining Area. Result of this study show that fractures in Bende Area is dominated by extension fractures and stylolite. Lithological control in fractures distribution can be seen in stilolit intensity, where is in headcoral-platycoral facies have lower intensity value than platycoral bindstone facies. Structural control in fractures intensity are shown in extensional fractures intensity. Here, fault affected area about 1-2.5 m related to fault position. Fracture position related to fold will be differentiating type and distribution of fractures.